Systemic administration of IL‐33 induces a population of circulating KLRG1hi type 2 innate lymphoid cells and inhibits type 1 innate immunity against multiple myeloma. Issue 1 (18th September 2020) - Guillerey, Camille; Stannard, Kimberley; Chen, Jason; Krumeich, Sophie; Miles, Kim; Nakamura, Kyohei; Smith, Jessica; Yu, Yuan; Ng, Susanna; Harjunpää, Heidi; Teng, Michele WL; Engwerda, Christian; et al.
Abstract: Type 2 innate lymphoid cells (ILC2s) are important producers of type 2 cytokines whose role in hematological cancers remains unclear. ILC2s are a heterogeneous population encompassing distinct subsets with different tissue localization and cytokine responsiveness. In this study, we investigated the role of bone marrow (BM) ILC2s and interleukin (IL)‐33‐stimulated ILC2s in multiple myeloma, a plasma cell malignancy that develops in the BM. We found that myeloma growth was associated with phenotypic and functional alterations of BM ILC2s, characterized by an increased expression of maturation markers and reduced cytokine response to IL‐2/IL‐33. We identified a population of KLRG1 hi ILC2s that preferentially accumulated in the liver and spleen of Il2rg −/− Rag2 −/− mice reconstituted with BM ILC2s. A similar population of KLRG1 hi ILC2s was observed in the blood, liver and spleen of IL‐33‐treated wild‐type mice. The presence of KLRG1 hi ILC2s in ILC2‐reconstituted Il2rg −/− Rag2 −/− mice or in IL‐33‐treated wild‐type mice was associated with increased eosinophil numbers but had no effect on myeloma progression. Interestingly, while decreased myeloma growth was observed following treatment of Rag‐deficient mice with the type 1 cytokines IL‐12 and IL‐18, this protection was reversed when mice received a combined treatment of IL‐33 together with IL‐12 and IL‐18. In summary, our data indicate that IL‐33 treatment induces a population of circulating inflammatory KLRG1 hi ILC2s and inhibits type 1 immunity against multiple myeloma. These results argue against therapeutic administration of IL‐33 to myeloma patients. Abstract : Multiple myeloma growth is associated with altered phenotype and function of type 2 innate lymphoid cells (ILC2s) in the bone marrow. In this study, we showed that treatment with the ILC2‐activating cytokine interleukin (IL)‐33 inhibits type 1 immune responses to IL‐12 and IL‐18 and facilitates myeloma growth.